2002
DOI: 10.2355/isijinternational.42.916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nb on the Proof Strength of Ferritic Stainless Steels at Elevated Temperatures.

Abstract: The effect of Nb on the high temperature proof strength of 0.46 % Nb-added ferritic stainless steel was studied from the viewpoints of solid solution strengthening, precipitation strengthening, and precipitation strengthening during tensile test and/or preceding hold time. The results obtained were as follows.(1) The increase in high temperature proof strength in Nb-added ferritic stainless steel is particularly remarkable at around 700°C in comparison with that in Ti-added steels.(2) After aging treatment for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…7,8) [ [6][7][8] were plotted. The data were experimentally obtained by the extracted residues from 0.01C-0.01N-18Cr-0.5Nb-2Mo mass% steel aged at 950°C for Fe 3 Nb 3 C 6) and 0.008C-0.007N-15Cr-0.46Nb-0.08Mo mass% steel aged at 700°C for Fe 2 Nb 7,8) respectively. The solubility products obtained here are good agreement with the experimental data in the previous literatures.…”
Section: Verification With Experimental Data In Literaturesmentioning
confidence: 99%
“…7,8) [ [6][7][8] were plotted. The data were experimentally obtained by the extracted residues from 0.01C-0.01N-18Cr-0.5Nb-2Mo mass% steel aged at 950°C for Fe 3 Nb 3 C 6) and 0.008C-0.007N-15Cr-0.46Nb-0.08Mo mass% steel aged at 700°C for Fe 2 Nb 7,8) respectively. The solubility products obtained here are good agreement with the experimental data in the previous literatures.…”
Section: Verification With Experimental Data In Literaturesmentioning
confidence: 99%
“…[5][6][7] Generally, solute Nb is readily precipitated out as carbonitride when the steel used at high temperature for a long time, the high temperature strength can be affected due to the Nb(C,N) precipitation in Nb containing ferritic stainless steel. 8) As strong forming elements of carbide and nitride, the precipitation evolution of Nb and V depends on various factors, such as liquid/solid condition, solid solubility, and interaction of other elements. 9) The previous study show that the introduction of small amounts of rare earth (RE) elements, such as yttrium, cerium, lanthanum, is beneficial to improve the mechanical properties, the high-temperature oxidation resistance and the corrosion resistance in niobium containing steels, 10,11) these effects has been proved to be induced by RE and reactive element effect.…”
Section: Introductionmentioning
confidence: 99%
“…Nabiran et al [5] reported that the contribution due to the rapid coarsening of Laves phase precipitates to the high-temperature strength was comparatively small. On the other hand, it was reported that Nb forms several different types of precipitates around 900°C that could degrade high-temperature strength and thermal fatigue resistance [6]. Morrie et al [8] noted that rapid coarsening of the Laves phase at high temperatures significantly reduces strength over 973K(700°C), and Sim et al [9] reported that coarse, rod-shaped Laves phase precipitates (Fe 2 Nb) formed at 973K(700°C) are very detrimental to high-temperature strength of Nbcontaining steels.…”
Section: Introductionmentioning
confidence: 99%
“…Niobium-(Nb) containing ferritic stainless steels were developed to overcome the lower high-temperature strength [1][2][3]. Niobium improves high-temperature strength and thermal fatigue resistance by solid-solution hardening and precipitation hardening [4][5][6][7][8][9]. Fujita et al [4] reported that fine Nb carbo-nitrides and Nb-based Laves phase precipitates formed during hightemperature deformation improve the strength of the alloy at 1173K(900°C).…”
Section: Introductionmentioning
confidence: 99%